Public key encryption with equality test for vehicular system based on near-ring. (20th August 2022) - Muthukumaran, V.; Ezhilmaran, D.
In recent years, vehicles are increasingly integrated with an Intelligent Transport System (ITS). This lead to the development of Vehicular Ad hoc Networks (VANETs) through which the vehicles communicate with each other in an effective manner. Since VANET assists in both vehicle to vehicle and vehicle to infrastructure communication the property of security and privacy has become the major concern. In this context, this work presents a Public Key Encryption with Equality Test based on DLP with decomposition problems over near-ring. The proposed method is highly secure and it solves the problem of quantum algorithm attacks in VANET systems. Further, the proposed system is highly secure and it prevents the chosen-ciphertext attack in type-I adversary and it is indistinguishable against the random oracle model for the type-II adversary. The proposed scheme is highly secure and the security analysis measures are comparatively stronger than existing techniques.